IATROGENIC BILE DUCT INJURIES: EXPERIENCE AT PIMS - Bakhsh, Rasool; Zahid, MA; Dar, Faisal Saud; Malik, Zafar Iqbal; Akhtar, Noor; Akhtar, Samia (Journal of Ayub Medical College Abbottabad, 2002)
Background: Cholecystectomy is one of the most familiar and commonly performed elective operation in general surgery. However, bile duct injury is a rare but one of the worst complications of this procedure. Although infrequent in expert hands, it is usually encountered when comparatively inexperienced surgeons are operating. These injuries present at variable time after the primary surgery. The prompt recognition and active management affects the morbidity and mortality associated with it. We evaluated the data of the hospital to find out the nature of injuries inflicted to extra hepatic bile duct and its management. Methods: This is a study of 20 cases of iatrogenic bile duct injury managed at the Department of Surgery Unit 1, PIMS. The study includes cases that had undergone cholecystectomy, open or laparoscopic in previous 11 years and sustained injury to the biliary tree and were managed accordingly. Patients with hepatobiliary malignancy were excluded. Results: Twenty cases were found to have various types of bile duct injuries. All patients were females, and their average age was 35 years. In four cases the injury occurred during surgery at our hospital, while remaining 16 cases were referred from other hospitals. All the patients were explored and managed accordingly. They had uneventful recovery and had good outcome at 6 months. Conclusion: Although the fact is that, the sooner an injury is recognized and treated, the better is the outcome. However, in this study the duration of injury had no effect on final outcome. KEYWORDS: Bile duct injuries, Cholecystectomy, Iatrogenic.